2020
DOI: 10.1108/jhr-06-2019-0125
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of patients' knowledge, attitudes and practices (KAP) regarding uncomplicated malaria in the primary healthcare facilities of Plateau state, Nigeria

Abstract: PurposeThis study determined factors that influenced patients' knowledge, attitudes and practices (KAP) regarding uncomplicated malaria in primary healthcare (PHC) facilities of Plateau state, Nigeria.Design/methodology/approachThe data of 956 patients treated for uncomplicated malaria in PHC facilities of Plateau state were used for the study. Inferential statistical analyses were conducted to identify factors that influenced patients' KAP on the disease and its management.FindingsThe study revealed age (p &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
3
1
Order By: Relevance
“…Regarding the age groups, most of the respondents aged 26 years and above had a high knowledge, with a large proportion of these being in the 36–40 years age group. This is in contrast to a study by Jimam and Ismail [ 40 ], who determined the predictive factors of KAP on uncomplicated malaria. Although those researchers showed that age was significantly associated with the level of knowledge, as was seen in this study, they revealed a likely decrease in KAP with increased age of the patients.…”
Section: Discussioncontrasting
confidence: 79%
“…Regarding the age groups, most of the respondents aged 26 years and above had a high knowledge, with a large proportion of these being in the 36–40 years age group. This is in contrast to a study by Jimam and Ismail [ 40 ], who determined the predictive factors of KAP on uncomplicated malaria. Although those researchers showed that age was significantly associated with the level of knowledge, as was seen in this study, they revealed a likely decrease in KAP with increased age of the patients.…”
Section: Discussioncontrasting
confidence: 79%
“…It is worth to note that the findings of the present study and other research [17,27] showed that the improvement in nutrition knowledge enhances the practice of high dietary diversity, which is associated with a high level of edu cation. The least consumed food groups were organ meat and milk, which was similar to findings from other studies [24,25].…”
Section: Discussionsupporting
confidence: 67%
“…It also may imply that increasing educational attainment allows an individual to acquire more knowledge on basic nutrition from other sources of information [22]. Also, improvement in nutrition knowledge as family monthly income increases may be explained by the fact that low-income earners are faced with challenges of meeting up with family needs, and may not have the time and resources to acquire more nutrition knowledge, unlike those with increased family income who may be eager to improve their diet through the acquisition of more nutrition knowledge [27]. Furthermore, respondents who had one to two children in their households were 2 times more likely to have high dietary diversity com-pared to those with more than two children.…”
Section: Discussionmentioning
confidence: 99%
“…KAP was used to measure the extent to which any clear opposition to family planning existed among different populations, so specific family planning practices could be used for different programs worldwide [ 31 ]. KAP surveys are now the most widely used studies for demonstrating societal context in public health research [ 32 34 ]. These surveys are easy to design, data output is quantifiable, interpretation is robust, and their utility is generalizable for context-specific problems [ 35 ].…”
Section: Methodsmentioning
confidence: 99%